Feasibility of Substitution of the Conventional Street Lighting Installation by the Photovoltaic Case Study on a Municipality in Agadir in Morocco - Fatima Outferdine; Lahoussine Bouhouch; Mustapha Kourchi; Mohamed Ajaamoum; Ali Moudden (Institute of Advanced Engineering and Science, 2017)
In this work, we present a technical and economic study of the solar powered street lighting system of a municipality in the south of Morocco. The state of the conventional street lighting system is first analyzed in a substation of street lighting. Then a sizing method is applied to the photovoltaic installation in the testing area. A financial study, by comparison between conventional and PV-based lighting, is carried out showing the feasibility of the PV street lighting.